The Effect of Hexagon Fraud on Fraudulent Financial Statements, Moderated by Audit Quality (A Case Study of Hospitals Listed on the Indonesia Stock Exchange) - Aretha Bening Topayung; Lintje Kalangi; Claudia W.M. Korompis (International Journal Labs, 2026)
This study investigates the effect of Fraud Hexagon components on fraudulent financial statements (FFS) in hospitals listed on the Indonesia Stock Exchange (IDX), with audit quality as a moderating variable. The research examines factors including Pressure (financial targets and liquidity), Capability (CEO education), Opportunity (nature of industry and audit committee oversight), Rationalisation (auditor changes), Arrogance (CEO narcissism), and Collusion (internal and external cooperation). A quantitative approach was applied using secondary data from 23 hospitals with complete financial and audit information for the 2020–2024 period. Data were analysed using regression models to test the influence of Fraud Hexagon elements on FFS and the moderating effect of audit quality. The results indicate that each Fraud Hexagon component significantly contributes to fraudulent reporting, while high-quality audits can effectively moderate these relationships, reducing the likelihood and severity of FFS. This research contributes to improving fraud detection mechanisms, strengthening internal control systems, and informing stakeholders of the critical role of audit quality in mitigating financial misreporting in healthcare institutions.